The Influence of Financial Literacy and Lifestyle on Consumptive Behavior in Class XI Accounting and Finance Students at SMK Negeri 1 Pematangsiantar: Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Perilaku Konsumtif pada Siswa Kelas XI Akuntansi dan Keuangan Lembaga SMK Negeri 1 Pematangsiantar - Ginting, Delfi Riana; Gultom, Binsar Tison; Simamora, Benjamin Albert (ITScience (Information Technology and Science), 2024)
Currently, many students are too consumptive because they cannot manage their finances well. Having good financial knowledge is one way to reduce the negative impact of students' ignorance in managing finances. Planning needs to be done to anticipate financial problems. This type of research is associative research using a quantitative approach. The population in this study was 100 students consisting of classes XI AKL 1, XI AKL 2, The results of the research show that the partial test (t test) of the financial literacy variable is 0.722 < from t table with df= n-k (100-2=98) of 1.660 or a significance of 0.472 > 0.05, so H0 is accepted and Ha is rejected. It can be interpreted that financial literacy does not have a positive effect on consumer behavior. The t-test value on the variable It can be concluded that lifestyle has a positive effect on consumer behavior. Simultaneously, the Fcount value from the table is 34.274 with Ftable (100-2-1=97) of 3.09 where Fcount > Ftable and significance is 0.000 < 0.05, so H0 is rejected, meaning that financial literacy and lifestyle simultaneously have a positive effect on behavior. consumptive. Based on the calculation results obtained by the researcher using SPSS 21, it can be seen that the coefficient of determination test (R2) where the resulting R square is 0.414, which means that the coefficient of determination is 41.4%, namely Financial Literacy (X1) and Lifestyle (X2), while the rest is influenced by other variables amounting to 58.6%.